Penentuan Kadar Alkaloid Total Ektstrak Akar Bajakah (Spatholobus Littoralis Hassk) dengan Metode Spektofotometri Uv-Vis - Hanifah, Nur; Daulay, Anny Sartika; Rahman, Fatur; Nasution, Haris Munandar (Journal of Pharmaceutical and Health Research, 2024)
The Bajakah tampala tree (Spatholobus littoral hassk) is a native plant from the interior of the forests in Kalimantan, especially Central Kalimantan. This plant is a plant that stretches or grows and grows abundantly in the interior of the forest. The Bajakah plant is known to the people of Kalimantan as a medicinal plant and can cure various diseases, including diarrhea, rheumatism, and cancer. The aim of this research was to determine the alkaloid content of bajakah root extract in various concentrations. The research method was carried out experimentally, with the independent variable being an ethanol extract of bajakah roots with concentrations of 50, 70, and 96%. Meanwhile, the dependent variables are the characteristics of simplicia, the secondary metabolite content of Bajakah root ethanol extract, and the determination of the total alkaloid content of Bajakah root extract. Bajakah root simplicia extract is made with 96, 70, and 50% ethanol solvents. The parameters used in this study include water content, total ash content, acid insoluble ash content, water soluble extract content, ethanol soluble extract content, and secondary metabolite content, including alkaloids, tannins, flavonoids, saponins, steroids, and terpenoids, by conducting phytochemical screening. , making a standard caffeine solution, determining the maximum wavelength of caffeine, measuring the caffeine calibration curve, and determining the total alkaloid content of Bajakah root extract. The results of the phytochemical screening showed that Bajakah root was positive for containing alkaloid compounds, saponins, tannins, flavonoids, steroids, and terpenoids. And the results obtained from Bajakah root plants obtained from Central Kalimantan were a 96% ethanol concentration of 1.66797 ± 0.7088 mg/gram, a 70% ethanol concentration of 1.6679 ± 0.1124 mg/gram, and a 50% ethanol concentration of 0.46981 ± 1.0656 mg/gram